2017
DOI: 10.1002/bit.26478
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics and transcriptomics analysis‐guided metabolic engineering of Propionibacterium acidipropionici for improved propionic acid production

Abstract: Acid stress induced by the accumulation of organic acids during the fermentation of propionibacteria is a severe limitation in the microbial production of propionic acid (PA). To enhance the acid resistance of strains, the tolerance mechanisms of cells must first be understood. In this study, comparative genomic and transcriptomic analyses were conducted on wild-type and acid-tolerant Propionibacterium acidipropionici to reveal the microbial response of cells to acid stress during fermentation. Combined with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
(67 reference statements)
3
20
0
Order By: Relevance
“…Relatively few genetic modification studies have been performed in propionibacteria (Gonzalez‐Garcia, McCubbin, Navone et al ; Guan et al, ; Liu et al, ) due to the limited availability of genetic modification tools. The alternative, random mutagenesis in propionibacteria , has successfully delivered economically viable strains (Luna‐Flores, Stowers, Cox, Nielsen, & Marcellin, ); however, quite often little learning results from random approaches (Jang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few genetic modification studies have been performed in propionibacteria (Gonzalez‐Garcia, McCubbin, Navone et al ; Guan et al, ; Liu et al, ) due to the limited availability of genetic modification tools. The alternative, random mutagenesis in propionibacteria , has successfully delivered economically viable strains (Luna‐Flores, Stowers, Cox, Nielsen, & Marcellin, ); however, quite often little learning results from random approaches (Jang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The ΔldhA strain did not show a significant increase in propionate production but increased 1-propanol threefold. Interestingly, the ΔldhA knockout in P. acidipropionici reported by Guan et al (2018) showed a detrimental effect on both biomass production and propionate yield associated with an imbalance in the NADH/NAD+ ratio. 1-Propanol production, thus, seems to alleviate this imbalance.…”
mentioning
confidence: 99%
“…acidipropionici-ΔpoxB-Δldh [17]. A further 37.1% increase of PA titer (28.1 ± 0.96 g•L − 1 vs. 38.7 ± 1.14 g•L − 1 ) and 37.8% increase of PA productivity (0.216 ± 0.006 g…”
Section: Resultsmentioning
confidence: 98%
“…Liu et al improved the PA titer of P. jensenii by 34.7% by overexpressing phosphoenolpyruvate carboxylase (ppc) and deleting lactate dehydrogenase (ldh) [11]. Guan et al obtained a 12.2% increase of PA by constructing a P. acidipropionici strain with simultaneous deletions of ldh1, ldh2 and pyruvate oxidase (poxB) [17]. However, combining metabolic engineering with laboratory evolution to improve the synthesis of PA has not been published, and may be a successful strategy.…”
mentioning
confidence: 99%
“… Liu et al (2016) improved the PA titer of P. jensenii by 34.7% by overexpressing phosphoenolpyruvate carboxylase ( ppc ) and deleting lactate dehydrogenase ( ldh ). Guan et al (2018) obtained a 12.2% increase of PA by constructing a P. acidipropionici strain with simultaneous deletions of ldh 1, ldh 2 and pox B. Evolutionary engineering, also defined as adaptive laboratory evolution, is a popular approach to develop high-performing strains for industrial application ( Mans et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%